2020
DOI: 10.1097/ana.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Management of Endovascular Treatment for Acute Ischemic Stroke During the COVID-19 Pandemic at a Single Institution in Beijing, China: A Brief Report

Abstract: Background: The coronavirus disease (COVID-19) pandemic is currently a major challenge for health care systems around the world. For a time-sensitive emergency such as acute ischemic stroke (AIS), streamlined workflow times are essential to ensure good clinical outcomes. Methods: The aim of this single-center, retrospective, observational study was to describe changes in stroke workflow patterns and clinical care during the COVID-19 pandemic. Data from AIS patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A study from Asia examined orthopedic surgery charges and found similar if not reduced in-hospital costs for orthopedic procedures (both urgent and elective) during the pandemic relative to pre-pandemic [24]. Another study from China regarding acute ischemic stroke, however, observed the opposite effect, with higher hospitalization costs during the height of the pandemic there [25]. Based on these findings, further cost studies in other areas of clinical medicine, in particular those requiring direct patient intervention and other activities that cannot be completed via telemedicine, are encouraged.…”
Section: Plos Onementioning
confidence: 99%
“…A study from Asia examined orthopedic surgery charges and found similar if not reduced in-hospital costs for orthopedic procedures (both urgent and elective) during the pandemic relative to pre-pandemic [24]. Another study from China regarding acute ischemic stroke, however, observed the opposite effect, with higher hospitalization costs during the height of the pandemic there [25]. Based on these findings, further cost studies in other areas of clinical medicine, in particular those requiring direct patient intervention and other activities that cannot be completed via telemedicine, are encouraged.…”
Section: Plos Onementioning
confidence: 99%
“…The inconsistent nding may be related to the rapid rise and younger incidence of stroke in China [34]. The average age of stroke in China was about 65 years old, lower than that in developed countries, about 75 years old [35]. In fact, due to the relative improvement of risk awareness in the elderly from China, combined with lifestyle changes and lipid-lowering drugs, the risk of dyslipidemia and the incidence of cardiovascular and cerebrovascular diseases can be reduced to a certain extent.…”
Section: Discussionmentioning
confidence: 98%
“…The inconsistent finding may be related to the rapid rise and younger incidence of stroke in China. The average age of stroke in China was about 65 years old, lower than that in developed countries, about 75 years old [28]. In fact, due to the relative improvement of risk awareness in the elderly from China, combined with lifestyle changes and lipid-lowering drugs, the risk of dyslipidemia and the incidence of cardiovascular and cerebrovascular diseases can be reduced to a certain extent.…”
Section: Discussionmentioning
confidence: 99%